Investigating business process changes: a framework for identifying outdated process models - Avila, Diego Toralles; Sanchez, Encarna Sosa; Fantinato, Marcelo; Polančič, Gregor; Thom, Lucineia Heloisa (Business process management journal, 2025)
PurposeDue to a lack of event data, organizations using Business Process Management may struggle to update their process models whenever business process changes occur. As such, alternative data sources are needed to detect and monitor business process changes.Design/methodology/approachWe conducted interviews with domain experts to analyze real business processes and classify any identified changes using Reijers and Mansar's framework on business process redesign heuristics. Based on the results, we proposed a taxonomy of entity groups as well as a method for identifying entities in process models based on the taxonomy. With this method, we define how to create a mapping between entities and process models, forming a framework to identify outdated process models through monitoring the entities.FindingsThe analyses of 25 business processes let us define three entity groups that form our taxonomy. We confirmed the feasibility of our entity identification method by classifying process elements of 85 pre-existing process models according to the taxonomy. Regarding the mapping that forms the basis of our framework, we found it necessary to define requirement recommendations to ensure its consistency and rigor.Originality/valueThis study offers a novel approach to handling the challenges of business process change. By emphasizing the identification and use of entities in the analysis of business process changes, it provides a holistic approach to monitoring the work systems of an organization.